(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The aim of this study was to prepare sustained release (SR) suppositories containing Aceclofenac microspheres. In the first part of the study, Aceclofenac microspheres were prepared by solvent evaporation method employing ethyl cellulose as a microsphere forming polymer. The effect of drug: polymer ratio and stirring rate on microspheres formation, average particle size, incorporation efficiency, micromeritic properties and in vitro Aceclofenac release were investigated. The highest drug loading capacity was found with 1:1 drug- polymer ratio stirring rate caused insignificant effect on drug loading capacity. In the second part, SR suppositories were formulated by incorporating Aceclofenac microspheres having the highest drug loaded. The bases used were PEG 4000, PEG 6000 and stearic acid. The drugs released were evaluated by in vitro dissolution tests. Comparative results of SR suppositories containing Aceclofenac microspheres with that of conventional ones showed that the former has sustained effect up to 8 h in vitro.